Educational Activities for Older Adults Development in Lithuanian Social Care Institutions - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article reviews educational activities for older adults in social care institutions. The growing numbers of older people in the society create an imperative to keep reviewing and adapting for the newly emerging needs societal resources in the areas of social security, economics, education, and health care. Recent discussions about the potential of institutional social care to meet societal needs are gaining momentum in Lithuania and the challenge is to offer alternative, equally agreeable, forms of social care as, for example, social care of the adults at their own homes, involvement of non-governmental organisations into the provision of social and educational service provision. However, it is broadly accepted that social care provided for older adults in the social care institutions plays an important role in the provision of social and educational services and will continue to play this role in future.